Peningkatan Kapasitas Pelaku Usaha Mikro melalui Pendampingan Penyusunan Laporan Keuangan Berbasis Aplikasi SI APIK di Kawasan Wisata Aek Sijorni - Nurdelila; Yusuf Pathuansyah; Rizky Mery Octavianna Lubis (Yayasan Perguruan Kampus, 2026)
Micro-enterprises are a strategic sector that significantly contributes to economic growth and employment generation, particularly in tourism areas. However, most micro-enterprise owners continue to face challenges in financial management, including the absence of systematic financial reporting and the limited use of digital technology for recording business transactions. Similar issues were identified among micro-enterprises operating in the Aek Sijorni Tourism Area, South Tapanuli Regency, Indonesia. This article presents a simulated community service project aimed at enhancing the capacity of micro-enterprise owners through assistance in preparing financial statements using the SI APIK (Financial Information Recording Application System). The program adopted a Participatory Action Research (PAR) approach, consisting of needs assessment, financial literacy training, SI APIK application training, hands-on assistance in preparing financial statements, and monitoring and evaluation. In this simulation, the program involved 30 micro-enterprise owners. Program evaluation was conducted using pre-tests, post-tests, skills observation, and participant satisfaction questionnaires. The illustrative results indicated that the participants' average score increased from 51.5 in the pre-test to 85.4 in the post-test, representing an improvement of 33.9 points. Participants' ability to use the SI APIK application improved from 43.2 to 88.4, while the overall satisfaction level reached 94%. The SI APIK-based mentoring program demonstrates the potential to enhance financial literacy, improve financial statement preparation in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), and accelerate the digital transformation of micro, small, and medium enterprises (MSMEs). This mentoring model has the potential to be replicated in other tourism destinations with similar socio-economic characteristics.